Pemikiran Komunikasi Dakwah Syekh Nawawi Albantani - Atoillah, Saifi; Zuhriah, Luluk Fikry (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study examines the communication thinking of Sheikh Nawawi Albantani's da'wah through a qualitative literature research approach through quotations contained in several of his books which are full of da'wah scientific treasures. Sheikh Nawawi Albantani is nicknamed the father of Indonesia's yellow book, even his knowledge is recognized and famous abroad as evidenced by Sheikh Nawawi once being a teacher in the city of Mecca, this is the religion that makes researchers interested in reviewing some of his works related to da'wah communication thinking, which may still be relevant to the world of da'wah today. The results of this study emphasize the thinking of da'wah communication which refers to the importance of paying attention to the target object of da'wah, using da'wah methods with soft words, upholding amar ma'ruf nahi munkar and prioritizing the oneness of Allah when delivering da'wah, which are things that need to be deepened for da'wah activists for the sake of the sustainability of religious syi'ar.